Definition and visualization of the context socio-ecological type (CSET). - Fradi, Fajr; Le, Quang Bao; Bonaiuti, Enrico; Thomas, Richard; Lala-Pritchard, Tana; Holmes, Holly Anne (2017)
The GeOC tool is divided in 2 components: the web-based geographic information system (called WEB-GIS tool) and the Sustainable Land Management (called SLM tool). This videos focus on WEB-GIS interface. This video shows how a context socio-ecological type can be defined and which the different outputs that the GeOC offers are. To check the GeOC tool, please follow this link: http://geoc.mel.cgiar.org To learn more about the project under which the GeOC tool is developed, please follow this link: https://mel.cgiar.org/projects/geoxc Acknowledgments: 'GeOC is the result of the synergic efforts by CGIAR Research Program on Dryland Systems (CRP-DS), the International Center for Agricultural Research in the Dry Areas (ICARDA) and its Geoinformatics Unit (GU), and is powered by iMMAP, Codeobia, D-Space and Amazon Web Services.'